Stakeholder Perception and Awareness on the Causal Relationship between Mining Exploitation and Environmental Degradation in Minahasa Region Indonesia - Kalalo, Flora P. (International Journal of Energy Economics and Policy, 2019)
Bangka Island in North Sulawesi is home to several endemics and endangered terrestrial and marine wildlife and at the same time a well-known tourist destination is facing a serious threat to irreversible environmental destruction due to mining activities. Although finally ordered closure by Indonesian Supreme Court, the initial mining activities have greatly impacted the highly critical environment of Bangka Island. This study aims to examine the documents (including government-issued permits as well as related laws and regulations) and interviewed key respondents as to their knowledge of the supposed mining activity and their perceived impacts. Results revealed that there were lapses in the Indonesian government's side in issuing permits. The respondents (N = 34) were fully aware of the natural resources (including mineral resources being mined) and identified mining as the major threat to the sustainability of the livelihood (tourism and fishery) that highly depend on the fragile island ecosystem of Bangka Island. We showed using a multivariate non-metric multidimensional scaling based on the respondents' attitude or perception towards the mining activities in Bangka Island. Regardless of their educational status, age, and occupation, it appears that the respondents have negative perceptions towards mining and openly suggest that mining be stopped. We identified major failures on the side of the government and the mining operators, including lack of proper consultation among stakeholders as well as failure to recognize the fragile condition (i.e. as a small island ecosystem) of Bangka Island as indicated in Indonesian laws and regulations related to zoning and utilization. Keywords: Bangka Island, Environment, Mining, North Sulawesi, Permits, Tourism, Zoning JEL Classifications: L72, Q30 DOI: https://doi.org/10.32479/ijeep.7689